1997
DOI: 10.1002/jhrc.1240201104
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on supercritical carbon dioxide extractions of hydrocarbons from geological samples

Abstract: SummaryThe extraction of aliphatic and aromatic hydrocarbons from New Albany Shale by supercritical carbon dioxide at different extraction temperatures is described. The main goal of this work was to determine the effect of the temperature on the extraction process (ie. relative extraction rate and efficiency). The data suggest that temperature changes of 20 and 40 degrees for the relatively moderate extraction temperatures tested (55, 75, and 95 "C), can have significant effects on both relative extraction ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Four fractions of extractions at every extraction temperature were individually collected. 60-minute extractions were chosen based on previous experiments [13,15] to provide exhaustive or near-exhaustive extractions for each temperature studied. A 1899-ppm squalane standard solution was prepared by weighing 0.0959 g of squalane (99%) in a 50-mL volumetric flask, mixing and diluting to volume with methylene chloride.…”
Section: Methodsmentioning
confidence: 99%
“…Four fractions of extractions at every extraction temperature were individually collected. 60-minute extractions were chosen based on previous experiments [13,15] to provide exhaustive or near-exhaustive extractions for each temperature studied. A 1899-ppm squalane standard solution was prepared by weighing 0.0959 g of squalane (99%) in a 50-mL volumetric flask, mixing and diluting to volume with methylene chloride.…”
Section: Methodsmentioning
confidence: 99%
“…This substitution can be done by molecules of a modifier and/or by other simple organic molecules mixed with the so-called polarity-shifting modifiers. Molecules of other compounds present in a sample, i. e., traces of water, etc., have also been found to be very helpful in some cases [17]. The removal of analytes bound in a matrix is often a time-consuming process.…”
Section: Sample "De-aging" During Extraction Static Phasementioning
confidence: 99%
“…Also, the extraction efficiency of PAH was found to be dependent on pressure and temperature, while that of phenols was not. JaffØ et al [17] observed the influence of temperature on the extraction of PAHs from clay soils. At mild temperatures (55, 75, and 958C), the yield of low-and high-molecular weight PAHs is increased exponentially and linearly, respectively.…”
Section: Introductionmentioning
confidence: 98%
“…Consequently, this results in an increase in solubility. However, the extraction efficiency exhibits an inverse relationship with the temperature: increasing the temperature at a constant pressure causes a decrease in CO 2 density. Additionally, the kinematic viscosity increases with a rising temperature. These lead to a reduction in the mass transfer coefficient, ultimately diminishing the extraction efficiency …”
Section: Introductionmentioning
confidence: 99%